Development of computer-assisted career guidance system for cognitive science undergraduates - Nigel, Wong Chee Foong (Universiti Malaysia Sarawak (UNIMAS), 2017)
Cognitive Science is a program offered by Universiti Malaysia Sarawak (UNIMAS) as an undergraduate program. The program covers a wide array oftopics and exposes the students to many different fields. The problem arises when the students do not know where their interest lies as the nature of their program does not provide them with a specific direction. As a result, they struggle to pursue a career in a field that interests them and this may result in low job satisfactions in the future. This project aims to provide a potential solution for this problem by developing a computer-assisted career guidance syst= to assist them in making the best possible career choice. The system makes use of the RIASEC personality inventory to determine the user's personality type and attempts to suggest them with careers which might interest them enough to pursue it. The questionnaire was adopted from the RIASEC personality inventory and the suggested careers were filtered to only include those which are relevant to Cognitive Science.